Threat Life Cycle and Its Dynamics - Rudolf Urban; Šárka Hošková-Mayerová (DETUROPE)
This article presents a discussion and reflection on the concept of monitoring the life cycle of threats. Furthermore, it indicates that due to the changing environmental conditions, for example, there may also be changes in the evaluation of not only the threat dynamics as a whole, but also of its various phases. This approach, with an emphasis on exploring the dynamics of each phase, is first tested on a hypothetical example. Subsequently, a verification of these considerations is conducted on the example of the development of specific threats - floods on two rivers.